2018
DOI: 10.1055/s-0044-100793
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Sensors are a Valid Tool to Detect and Consistently Quantify Jumping

Abstract: Considering the large and repetitive loads associated with jumping in team sports, automatic detection and quantification of jumping may show promise in reducing injury risks. The aim of this study was to validate commercially available inertial-movement analysis software to detect and quantify jumping in team sports. In addition, the test-retest reliability of the software to quantify jumping was assessed. Seventy-six healthy male participants completed a team sport circuit six times containing seven common m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 26 publications
0
25
2
Order By: Relevance
“…The dwell time or minimum effort duration (MED) in the present study was set to 0.4 s, since Varley et al (2017) concluded that it was difficult to provide an appropriate MED with acceleration efforts. Jumps were registered as total jumps (tJUMP) and highintensity jumps (hJUMP, over 0.4 m) (Spangler et al, 2018). The DEC and ACC variables were defined as inertial movements registered in forward deceleration and acceleration vectors, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The dwell time or minimum effort duration (MED) in the present study was set to 0.4 s, since Varley et al (2017) concluded that it was difficult to provide an appropriate MED with acceleration efforts. Jumps were registered as total jumps (tJUMP) and highintensity jumps (hJUMP, over 0.4 m) (Spangler et al, 2018). The DEC and ACC variables were defined as inertial movements registered in forward deceleration and acceleration vectors, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies tested the FreePower [25,34]. Two studies tested the MinimaxX GPS [26,43]. The GPSport, Xsens Results of individual studies: validity of IMU for estimation of jump height Information on the validity levels obtained in the included studies can be found in Tables 4-7.…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 99%
“…After each session, the data were downloaded into a specialized analysis program (OpenField; Catapult Innovations, Melbourne, Australia-Version 1.22.2 Build #41409). Accelerometer variables and definitions are in Table 1 with a directional chart shown in Figure 1 (Spangler et al, 2018;Catapult Sports, n.d.).…”
Section: External Loadmentioning
confidence: 99%